Successful outcome of gestation in a young woman with severe oesophageal varices throughout the pregnancy. - Shamim, S; Nasrin, B; Chowdhury, SB (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2): 287-291 The abstract of this article is available on the PubMed website